Treatment with Rituximab in extensive bullous pemphigoid - recalcitrant to conventional treatment: a report of 2 cases - Safura, Be Be; Gopal, K. V. T.; Raju, P. V. Krishnam; Rani, B. Rekha (International Journal of Research in Dermatology, 2024)
Bullous pemphigoid (BP) is the most common autoimmune blistering disease requiring treatment with immunosuppressive medications; however, finding a therapy that has a sustained durable response and an acceptable side effect profile has been challenging. Rituximab (RTX) is a monoclonal antibody targeting CD20, a transmembrane protein expressed on B cells, causing B cell depletion. RTX has shown great efficacy in studies of pemphigus vulgaris, but data of pemphigoid diseases are limited. We report a 60 year old male who presented with widespread fluid filled lesions and raw areas preceded by itching since 3 weeks. Dermatological examination revealed multiple intact bullae, vesicles were seen over urticarial plaques and multiple raw areas, erosions with crust formation over trunk, upper and lower extremities. Histopathological examination (HPE) showed sub epidermal blister. Direct immunofluorescence (DIF) revealed IgG: positive (+3), C3: positive (+2), linear pattern, along the dermoepidermal junction. Based on the clinical features, HPE and DIF findings, diagnosis of BP was made. Patient did not respond to high dose of corticosteroids for 3 weeks. Second case was known case of BP who did not respond to conventional treatment even after 5 years. Both cases were treated with Rheumatoid arthritis protocol of RTX and marked improvement was seen after 8 weeks of treatment with no recurrence of lesions. Our experience shows that in all cases of extensive BP and cases not responding to conventional treatment, injection rituximab should be considered for in view of ease of administration, excellent safety profile and good efficacy.